Development Of Carbonated Hydroxyapatite (CHA) Porous Scaffolds For Bone Tissue Engineering Applications - Wong, Shi Chin (Universiti Sains Malaysia, 2018)
Carbonated Hydroxyapatite (CHA) powder was synthesized via nanoemulsion method and followed by physico-chemical characterizations. The synthesized CHA powder in this study was confirmed that was B-type CHA in calcium deficient. In the second part of the study, the interconnected porous CHA scaffold was fabrication by polyurethane (PU) sponge replica method. The study was to optimize the composition of CHA slurry by manipulating the type of CHA powders as well as the amount of binder and addition of kaolin to have improved the architecture of the scaffold. Sintering was then performed on the CHA scaffolds at 800℃ with two different heating rate of 5℃/min and 10℃/min for 2 hours. 5wt.% kaolin CHA scaffold with binder ratio of PEG: PVA = 2:3 sintered at 800℃ with heating rate of 5℃/min had the most optimum architecture. The optimum scaffold had 80.11% of apparent porosity with about 200-400 μm of macropores, regular thickness of strut with average of 30-50 μm with minimum crack and compressive strength of 0.072 MPa. It can be concluded that the heating rate used in this study showed the least impact in developing the CHA porous scaffolds whereas the key of success in fabrication CHA porous scaffolds in this study is mainly dependent on the compositions of the slurry used. In terms of bioactivity, kaolin CHA scaffold formed apatite layer on the surface of the scaffold after immersed in SBF for 7 days. This showed that kaolin CHA scaffold was suitable to be use in bone tissue engineering especially for non-bearing applications.